Fostering sustainable development : the sector investment program - Okidegbe, Nwanze (World Bank WashingtonUS, 1997)
Describes the rationale and analytical basis for Sector Investment Programs (SIPs) and the lessons learned through early implementation experience. Argues that SIPs can have a greater development impact that free standing projects because they address in a holistic manner the underlying conditions that often impede the effectiveness of development assistance. Makes a strong case that the World Bank and other donors should give greater consideration to SIPs as a way to improve the effectiveness of development assistance, especially in Africa and South Asia.